1995
DOI: 10.1088/0268-1242/10/7/009
|View full text |Cite
|
Sign up to set email alerts
|

The diffusion of Mn in CdTe

Abstract: The diffusivity of Mn in CdTe, D(Mn), has been measured between 500 and 800 "C under saturated Cd and Te condaions. The variation of D(Mn) with Cd partial pressure was measured at 600 'C. Between 500 and 800 "C D(Mn) = (22.5: 3.30)exp [(-(2.35 for saturated Te, and between 600 and 800 "C for saturated Cd D(Mn) = (1.12:9,12) x 1O3exp(-(2.76i0.18)eV/kT) cm2 s-', These results are consistent with those at 600 "C which show D(Mn) to increase with decreasing Cd partial pressure. It is argued that lhe observed feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 15 publications
(1 reference statement)
3
31
1
Order By: Relevance
“…[60] The last value considerably exceeds the band-gap of CdTe, Fig. 1 The best linear fits to the yield of solute-diffusion data collected in [4] : DE = 1.5 eV, confirming the existence of diffusing atoms in an excited state with the energy for the process that is much larger than that of a typical excitation.…”
Section: Diffusion Of Foreign Impurities In Cdtementioning
confidence: 68%
“…[60] The last value considerably exceeds the band-gap of CdTe, Fig. 1 The best linear fits to the yield of solute-diffusion data collected in [4] : DE = 1.5 eV, confirming the existence of diffusing atoms in an excited state with the energy for the process that is much larger than that of a typical excitation.…”
Section: Diffusion Of Foreign Impurities In Cdtementioning
confidence: 68%
“…While in synthetic systems the diffusion of the trace element (Mn) in semiconductors (CdSe) around temperature of 300 °C is negligible, 1-3 Å in short time (1 h) (Jamil and Shaw 1994), the equilibration and homogeneous distribution of the trace element within individual nanoparticles can be achieved over the geological time scale (Reich et al 2006;Deditius et al 2008;González-Jiménez et al 2015). Moreover, it was found that the formation of trace element-rich semiconducting NPswith homogeneously distributed doping element-is possible when the trace element is adsorbed on the growing surface of the nanocrystal (Erwin et al 2005).…”
Section: And References Therein) Substitution Of As For S In the Tetmentioning
confidence: 99%
“…In particular, one might expect that confinement could have a similar prominent effect on the diffusion of magnetic impurities in nanocrystals. Although it is known that the diffusion of Mn in bulk CdTe is very slow, with the overall diffusion barrier estimated experimentally to be more than 2 eV [10], diffusion in a nanosystem might be strongly modified by changes in the electronic structure as well as the much larger surface-to-volume ratio in nanocrystals when compared to bulk crystals.…”
mentioning
confidence: 99%
“…A detailed diffusion mechanism of Mn defects in CdSe nanocrystal is not clearly known; however, experiment has suggested that the diffusion of Mn atoms in bulk CdTe [10] and GaAs [19] involves interstitial defects. Thus, our work centers on the behavior of interstitial Mn atoms.…”
mentioning
confidence: 99%